Three decades of democratization in former soviet republics: Success or failure? - Ordukhanyan, Emil; Sukiasyan, Hayk; Shirinyan, Levon; Ananyan, Gohar (International Journal of Innovative Research and Scientific Studies, 2025)
The research explores the issue of democratization in former Soviet republics. Over the past three decades, these countries have experienced a wide range of political transitions, from nascent democracies to enduring autocracies. The core purpose of the research is to analyze the main theories of political transition and examine the main factors that have influenced the political trajectories in former Soviet republics, including their economic development, regional geopolitics, the role of international organizations, and domestic societal pressures. The research is conducted using the methodology of comparative analysis of relevant theories and concepts on democratization, as well as empirical and statistical data that are largely used to define the peculiarities of political transition in former Soviet republics. The study finds that while some republics have made significant strides toward democratic governance, others have faced setbacks or retreated into authoritarianism. The autocratic political culture inherited from the Soviet Union was maintained by Russian and some other post-Soviet rulers to foster their centralized power. This circumstance played a crucial role in democratization in the entire former Soviet region. The economic, energy, and security dependencies on Russia hindered political reforms in some republics that prioritized a democratic path of development. In others, democratic transitions were recognized as "color revolutions" supported by the West, aiming to strategically weaken Russia. In turn, Russia played the role of a locomotive to deter democratization not only on its territory but also in its near and far abroad. It is also concluded that domestic political efforts, international assistance, and Russia's geopolitical deterrence can reload successful democratization in former Soviet republics with a democratic vision.